Comparative gastroprotective effect of post‐treatment with low doses of rutin and cimetidine in rats. (3rd August 2011) - Olaleye, Mary Tolulope; Akinmoladun, Afolabi Clement
Abstract The anti‐ulcerogenic potentials of low doses of rutin and cimetidine in ethanol‐, acetic acid‐, and stress‐induced ulcers in rats have been evaluated and compared in this study. In each model, male Wistar rats were randomly divided into six groups (I–VI). Groups II–VI were administered 1 mL/100 g ethanol orally, 0.05 mL of 20% acetic acid submucosally or kept in a cold chamber for 6 h to induce ulcer in the ethanol‐, acetic acid‐, and stress‐induced ulceration model, respectively. Thereafter, group III was post‐treated with 300 mg/kg cimetidine and groups IV–VI with 20, 40, and 80 mg/kg rutin, respectively, while the control (group I) received distilled water in Tween 20. One hour after post‐treatment, all groups were killed and the gastric ulcer index was calculated. Malondialdehyde (MDA) level, vitamin C content, and glutathione peroxidase (GPx) activity were evaluated in the gastric mucosa of animals. Post‐treatment with rutin significantly reduced ulcerogen‐induced gastric damage in all models. This effect was significant at all dose levels compared with the ulcer‐induced groups. Rutin significantly reduced the MDA levels but increased the vitamin C content and GPx activity. Ulcer index and MDA level were highest in the ethanol‐induced ulcer model while vitamin C content and GPx activity were lowest in the stress‐induced ulcer model. The study showed that all three models of ulceration appeared to be linked to oxidative stress and also ascribed significant anti‐ulcerogenic potential to rutin especially at lower doses of 20–80 mg/kg.